Association Between 5α-Reductase Inhibitors and Prostate Cancer Mortality - Endah Lestari, Endah Lestari; Nur Fitriani, Nur Fitriani (International Medical Journal Corp. Ltd, 2024)
Background: The role of 5α-reductase inhibitors (5-ARIs) in managing prostate cancer has been a subject of considerable debate within the medical community. The exploration of these agents has evolved significantly over the years, reflecting both their therapeutic potential and the complexities associated with their use. Literature Review: The reviewed literature presents a multifaceted examination of 5α-reductase inhibitors (5-ARIs) and their implications for prostate cancer management. The introduction establishes a framework for understanding the evolving role of these agents, emphasizing both their potential therapeutic benefits and the concerns that have emerged regarding their use, particularly in relation to prostate cancer risk and mortality. Conclusion: In conclusion, the literature collectively indicates that while 5-ARIs possess therapeutic potential in managing prostate cancer, significant concerns regarding their safety profiles—particularly their association with high-grade tumors and implications for mortality—necessitate a cautious and informed approach in clinical practice. Future research should aim to elucidate the complexities of 5-ARIs, focusing on their integration with existing treatment protocols and the need for individualized patient care.